2013
DOI: 10.1016/j.foodpol.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported food insecurity in Africa during the food price crisis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 18 publications
5
66
0
1
Order By: Relevance
“…Empirical studies document these mixed impacts of food prices (Aksoy and Hoekman, 2010). The heterogeneity among households and countries is consistent with economic predictions: net sellers and exporters of food benefit and net buyers and importers lose; the transmissions of price shocks to local markets have been mitigated by policy interventions and by institutional and infrastructure deficiencies; and negative price effects on poverty and malnutrition have been offset by economic growth over the same period (Headey, 2013;Verpoorten et al, 2013). Accounting for positive wage effects for the rural poor significantly enhances the welfare benefits (Jacoby, 2013).…”
Section: Food Prices and Food Securitysupporting
confidence: 68%
“…Empirical studies document these mixed impacts of food prices (Aksoy and Hoekman, 2010). The heterogeneity among households and countries is consistent with economic predictions: net sellers and exporters of food benefit and net buyers and importers lose; the transmissions of price shocks to local markets have been mitigated by policy interventions and by institutional and infrastructure deficiencies; and negative price effects on poverty and malnutrition have been offset by economic growth over the same period (Headey, 2013;Verpoorten et al, 2013). Accounting for positive wage effects for the rural poor significantly enhances the welfare benefits (Jacoby, 2013).…”
Section: Food Prices and Food Securitysupporting
confidence: 68%
“…Like the country level studies by Headey (2013) and Verpoorten et al (2013), our household level study suggests that the food security and welfare consequences of food price and income shocks are highly context specific. Even in the same country, regional (structural) differences (e.g., speed of labor and commodity market adjustments, infrastructure and domestic policy responses) may significantly dictate the nature and extent of post-shock economic growth.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 74%
“…Critics argue that the core underlying assumptions (i.e., no responses to shocks) of the majority of these analyses may have resulted in an overestimation of the negative consequences. This argument has been further substantiated by recent studies examining the 'food price shock, food security and economic growth' nexus by Headey (2013) and Verpoorten et al (2013) Likewise, Verpoorten et al (2013) found that between 5 and 12 million people in 18 subSaharan African countries became more food secure over the period [2005][2006][2007][2008]. These studies concluded that the impacts of a food price shock on food security are highly context specific.…”
Section: Introductionmentioning
confidence: 93%
“…Consequently, studies which assume the inter-temporal validity of subjective indicators should be interpreted carefully, as this assumption is questionable (43,44) . Finally, the results raise the question of what the HFIAS actually measures and how households assess their own food security situation.…”
Section: Resultsmentioning
confidence: 99%